Bimbingan Perkembangan Remaja yang Beriman dan Bertaqwa - Nadzmi Akbar, S.Pd., M.PdI (UIN Antasari Banjarmasin, 2015)
Quality human Islamically besides mastering science and technology, but even more are all teenagers who have faith and devotion to God Almighty. Parents and educators have a responsibility to the development of quality youth Islami. One of the activities carried out in schools and Madrasah is the implementation of Guidance and Counseling. Guidance and counseling services can be designed to develop personal adolescents faithful and devoted. All forms and types of services can be used as a means to develop a personal faith and devoted.